Co-occurrence of Anti-N-Methyl-D-Aspartate Receptor Encephalitis and Anti-myelin Oligodendrocyte Glycoprotein Inflammatory Demyelinating Diseases: A Clinical Phenomenon to Be Taken Seriously - Ren, Yijun; Chen, Xiqian; He, Qiang; Wang, Renchun; Lu, Wei (Frontiers in Neurology, 2019)
Background: Anti-N-methyl-D-aspartate receptor (NMDAR) immunoglobulin G antibodies which exist on myelin sheaths, composed of oligodendrocytes, especially target GluN1 subunits and are highly characteristic of anti-NMDAR encephalitis which is a newly recognized autoimmune encephalitis (AE) characterized by psychiatric symptoms, behavioral abnormalities, seizures, cognitive impairment and other clinical symptoms. Myelin oligodendrocyte glycoprotein (MOG) is a type of protein which is expressed on the surface of oligodendrocytes and myelin in the central nervous system. Anti-MOG antibodies cause demyelination. In some rare reported cases, these two types of antibodies have been found to co-exist, but the underlying mechanisms remain unknown. Case presentation: Here we report cases of 4 inpatients (median age 31.5years-, age range 27-43-years) from The Second Xiangya Hospital of Central South University between March 2018 and April 2019. Two of the cases were first diagnosed as anti-NMDAR encephalitis and had developed visual impairments in the course of the dosage reduction during corticosteroid therapy. They were found at the time, to have anti-MOG antibody-positive CSF and/or serum. Another patient was diagnosed with anti-MOG inflammatory demyelinating diseases (IDDs) when he tested double positive for both anti-NMDAR and anti-MOG antibodies early in the course of his illness. Over the course of the dosage reduction during corticosteroid therapy, his symptoms deteriorated; however, anti-MOG antibody levels elevated while anti-NDMAR antibody levels remained low. The other patient had initially developed psychiatric symptoms and limb weakness. She was also double positive for anti-NMDAR and anti-MOG antibodies early in the course of her illness. However, over the course of the dosage reduction during corticosteroid therapy, her symptoms worsened and levels of both antibodies elevated. Conclusion: Anti-NMDAR and anti-MOG antibodies may coexist in rare cases. In addition, anti-NMDAR encephalitis and anti-MOG inflammatory demyelinating diseases may occur either simultaneously or in succession. Thus, when a patient is diagnosed with either of these two diseases, but exhibits symptoms of the other disease, the possibility of co-occurrence with both these diseases should be considered and the appropriate antibodies should be accurately detected to enable prompt selection of appropriate treatments by the physicians.